2017
DOI: 10.3991/ijet.v12i05.6967
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Educational Hypermedia Systems based on Learning Styles: the Case of Adaptation Rules

Abstract: Abstract-This paper investigates the pedagogical basis of Adaptive Educational Hypermedia Systems (AEHS) that incorporate Learning Styles in order to accommodate user's learning style preferences and needs. Therefore, AES adapt the learning content, its presentation and navigation to the user's learning style preferences. We collect thirty three (33) Adaptive and Intelligent Web-based Educational Systems (AIWBES) that incorporate learning styles and discuss twenty of them, namely the AEHS, as the remaining are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
1
13
0
3
Order By: Relevance
“…Recent Developments in e-learning interoperability standards, learning design and other research on the pedagogy of semantic e-learning have presented an inclination of Semantic Web technologies to encourage learning services focused on the learning content aware services and personalized [10][11][12]. Technologies based on ontologies and intelligent agents should support the processing of semantic information on the Semantic Web [13]. Most learning management system are currently working in a closed system.…”
Section: Semantic Web and E-learning Standards For Interoperabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent Developments in e-learning interoperability standards, learning design and other research on the pedagogy of semantic e-learning have presented an inclination of Semantic Web technologies to encourage learning services focused on the learning content aware services and personalized [10][11][12]. Technologies based on ontologies and intelligent agents should support the processing of semantic information on the Semantic Web [13]. Most learning management system are currently working in a closed system.…”
Section: Semantic Web and E-learning Standards For Interoperabilitymentioning
confidence: 99%
“…Some systems still use their own framework for learning the description of the content, instead of adopting the interoperability standard. The concept of course, student, pedagogical resource, summary or class must be formally described to be shared between all the systems of an educational institution [10][11][12][13].…”
Section: Semantic Web and E-learning Standards For Interoperabilitymentioning
confidence: 99%
“…According to the previous works, it can be concluded that a great deal of interest has been dedicated to studying and developing adaptive hypermedia systems in different educational systems (Tmimi et al, 2018;Tsortanidou et al, 2017). Also, some studies focused on the students' background, preferences, and cognitive abilities through developing the adaptive content presentation (Ahmadaliev et al, 2019;Kumar & Ahuja, 2020).…”
Section: Web-based Learningmentioning
confidence: 99%
“…The only disadvantage of the aforementioned works is that their system identifies students' preference during the class hours, the investigation gives the result gradually, maybe in the middle of the semester or in the end. Furthermore, most of the systems follow similar patterns [9]. To the best of our knowledge, in automatic methods, initializing the students' learning style in the beginning of the sessions is still lucking.…”
Section: Related Workmentioning
confidence: 99%